Pilot conversion trial from mycophenolic acid to everolimus in ABO‐incompatible kidney‐transplant recipients with BK viruria and/or viremia. (16th December 2015) - Belliere, Julie; Kamar, Nassim; Mengelle, Catherine; Allal, Asma; Sallusto, Federico; Doumerc, Nicolas; Game, Xavier; Congy‐Jolivet, Nicolas; Esposito, Laure; Debiol, Benedicte; Rostaing, Lionel
Summary: Immunosuppression using everolimus (EVR) plus low‐dose tacrolimus (Tac) is commonly used in organ transplantation. EVR has potential antiviral effects. Herein, the long‐term outcomes and impacts of Tac‐EVR on the BK virus are reported in ABO‐incompatible kidney‐transplant recipients. The initial immunosuppressive regimen combined steroids, Tac, and mycophenolic acid (MPA). At a median of 141 (34–529) days post‐transplantation, seven stable ABO‐incompatible kidney‐transplant recipients were converted from MPA to EVR because of active BK replication, and compared with a reference group of fourteen ABO‐incompatible patients receiving classical Tac plus MPA. At 1 month before conversion, at 1, 3 months after, and at last follow‐up, clinical and biological parameters were monitored. The median time from conversion to the last follow‐up was 784 (398‐866) days. Conversion to EVR caused no change to rejection episodes or immunological status (isoagglutinin titers, anti‐HLA antibodies). At last follow‐up, median eGFR was similar in the Tac‐MPA versus Tac‐EVR group (40 [range: 14–56] vs. 54.5 ml/min/1.73 m 2 [range: 0–128], P = 0.07). The major adverse event was dyslipidemia. Interestingly, conversion from MPA to EVR decreased BK viral load in five patients. ABO‐incompatible kidney‐transplant recipients with an active BK virus infection may benefit from conversion to EVR.